How to Build an Image‐Processing Pipeline for Automating Multiparameter Histocytometry Analysis. Issue 3 (16th March 2022) - Munoz‐Erazo, Luis; Schmidt, Alfonso J.; Shinko, Diana; Price, Kylie M.
Abstract: Until relatively recently, analysis of imaging data has been primarily quantitative and limited to 3‐4 markers. The advancement of various technologies overcoming this marker limitation provided the capability of analyzing multiparameter imaging data down to the single cell level, termed histocytometry. Currently, most published end‐to‐end histocytometric analysis of imaging data is performed using expensive commercial programs or freely available analysis packages that require significant knowledge of programming languages for execution. Here we present a protocol that performs cell segmentation, phenotyping and spatial analysis, using software with easy‐to‐use GUIs (graphical user interfaces). These protocols allow the user to derive spatial and phenotypical data for the analysis of multiparameter microscopic images from most imaging platforms in a low‐cost manner. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Cell Segmentation and generation of histocytometric .csv file Basic Protocol 2 : Phenotyping of cell populations Basic Protocol 3 : Spatial relationship analyses of phenotyped populations Support Protocol 1 : Nuclei Segmentation Accuracy Test Support Protocol 2 : Correcting y‐axis Inversion of Histocytometry Data Relative to Original Image File